2021
DOI: 10.1101/2021.01.06.425535
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Independent Genomic Sources of Brain Structure and Function

Abstract: IntroductionThe last decade has seen a surge in well powered genome-wide association studies (GWASs) of complex behavioural traits, disorders, and more recently, of brain structural and functional neuroimaging features. However, the extreme polygenicity of these complex traits makes it difficult to translate the GWAS signal into mechanistic biological insights. We postulate that the covariance of SNP-effects across many brain features, as be captured by latent genomic components of SNP effect sizes. These may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…In our previous, preliminary application of genomic ICA we provide evidence suggesting that many of the independent components indeed mapped to one or more of such underlying biological pathways 7 . In particular, we extracted independent components from GWAS output of thousands of brain-related traits from UK Biobank 17 .…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…In our previous, preliminary application of genomic ICA we provide evidence suggesting that many of the independent components indeed mapped to one or more of such underlying biological pathways 7 . In particular, we extracted independent components from GWAS output of thousands of brain-related traits from UK Biobank 17 .…”
Section: Introductionmentioning
confidence: 80%
“…While optimizing reproducibility is favorable, it has not been the only goal of our genomic source decomposition. Rather, we aimed at obtaining a latent representation of the genome-wide variant effect sizes that aligns more closely to coherent biological processes 7 . Our comparison of PCA and ICA demonstrated that with the exception of the first three (salient) PCA components, the rest of the PCA and ICA components are comparable with regards to cross-sample reproducibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,28 In the present paper, we present genomic PCA and ICA as novel, fully data-driven methods to decompose large, high-dimensional GWAS summary statistics. This work has evolved from our previous pilot work 29 and is therefore based on the same underlying rationale.…”
Section: Introductionmentioning
confidence: 99%
“…In the present paper, we present genomic PCA and ICA as novel, fully data‐driven methods to decompose large, high‐dimensional GWAS summary statistics. This work has evolved from our previous pilot work 29 and is therefore based on the same underlying rationale. In the present study, we present for the first time our complete and final methodological approach of genomic ICA, extended with PCA, along with a systematic evaluation of the robustness under a multitude of different analytic parameters, dimensionality of the output and other methodological considerations.…”
Section: Introductionmentioning
confidence: 99%